Hierarchical hollow microspheres Na3V2(PO4)2F3C@rGO as high-performance cathode materials for sodium ion batteries. (17th July 2020) - Du, Peng; Mi, Kan; Hu, Fangdong; Jiang, Xiaolei; Wang, Debao; Zheng, Xiuwen
Abstract : Nanosheet-assembled Na3 V2 (PO4 )2 F3 microspheres were synthesized by a one-step polyol-assisted hydrothermal method and combined with graphene as the cathode material for SIBs. Abstract : Sodium-ion batteries (SIBs) attract extensive attention as a promising alternative to lithium-ion batteries (LIBs) owing to their abundant reserves and low cost for large-scale energy storage systems. Among the electrode materials for sodium ion batteries, Na3 V2 (PO4 )2 F3 (NVPF), with the NASICON structure, has a unique three-dimensional (3D) channel, suitable voltage plateau and high thermal stability. However, it suffers from low intrinsic electronic conductivity. In this work, we successfully synthesize hierarchical hollow NVPF@C microspheres assembled from mesoporous nanosheets, and the possible formation process is systematically explored by changing the reaction time, solvent ratio and glucose dosage. At the same time, these microspheres are wrapped in graphene (marked as NVPF@C@rGO) to further improve their electrochemical performance. As a half-cell cathode, the NVPF@C@10 wt% rGO microspheres exhibit excellent rate performance (95 mA h g −1 at 2C) and cycle stability (78.2% capacity retention after 1500 cycles at 5C). This can be attributed to the hierarchical hollow morphology and graphene packages, which provide continuous electron and ion channels, large electrolyte contact areas and stable structures. This work will provide a viable method for designing high-power NIBs.